PEMBERDAYAAN PERAN SERTA MASYARAKAT DALAM PEMBIAYAAN PENDIDIKAN DI MA QUEEN AL KHOTIJAH CILACAP - Slamet Pamuji (Institut Agama Islam Darussalam Blokagung, 2023)
This study aims to describe the empowerment of community participation in financing education at MA Queen Al Khotijah Cilacap. This research is a descriptive research with a qualitative approach. The informants of this research were the principal and the school treasurer. Data collection methods used in the form of interviews, observation, and documentation. The validity of the data was tested by triangulation of techniques and sources. The data were analyzed qualitatively with the interactive model of Miles and Huberman. The results showed that the determination of education financing at the Ratu Al Khotijah Islamic High Court brought together the guardians of students to sit down and discuss. In the deliberation, the Supreme Court explained the plan for the MA's financing needs, especially for the payment of salaries for teachers and assistants. Then, the administrators and guardians of students agree and make joint decisions on the nominal amount that must be determined by the guardians of students every month. Not only that, as a form of report and evaluation, the administrator also reports to the guardians of the students related to their origin and monthly expenses at the student guardian meeting, especially those related to teacher and companion payments. In addition, there are also several donors who provide financing in MA apart from BOS funds